The uncommon reader - Bennett, Alan 1934- (Farrar, Straus and Giroux, 2007)
Obliged to borrow a book when her corgis stray into a mobile library, the Queen discovers a passion for reading, setting the palace upon its head and causing the royal head of Great Britain to question her role in the monarchy.
Keywords: Elizabeth / II / Queen of Great Britain / 1926- / Fiction; Elisabeth (Großbritannien, Königin, II.); Elizabeth <II, Queen of Great Britain, 1926-> -- Fiction; Elisabeth -- II. -- Großbritannien, Königin -- 1926-2022; Kings and rulers / Fiction; Queens / Great Britain / Fiction; Books and reading / Fiction; Bediensteter; Bekannter; Entdeckung; Leseinteresse; Books and reading -- Fiction; Kings and rulers -- Fiction; Queens -- Great Britain -- Fiction; Great Britain / Fiction; Großbritannien; Great Britain -- Fiction; Fiktionale Darstellung; Belletristische Darstellung; Humorous fiction